HUBUNGAN KELENTUKAN OTOT PUNGGUNG DAN DAYA LEDAK OTOT TUNGKAI TERHADAP KEMAMPUAN SMASH SEPAK TAKRAW EKSTRA KURIKULER SMA NEGERI 1 BENAI - Fitra Illahi; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The Problem in This Study is whether there is a Relationship Health Physical Education and Recreation of Teacher Training and education Riau University. of Teachers Training. The Purpose of This Study was to determine the significance of the Relationship Health Physical Education and Recreation of Teacher Training and education Riau University The Type of Research is Correlational. The Population used was PB Idila Siberakun athlete who numbered19 people. In the study of the variable relationship of back muscle flexibility to Sepak Takraw Smash, there is a positive and significant relationship with correlation coefficient of r = 0.879, the meaning is 6.898 means tcount (6.898)> t table (2.110), H0 is rejected H1 is accepted. . for the relationship of leg muscle explosive power variables to Sepak Takraw Smash, there is a positive and significant relationship with correlation coefficient of r = 0.956, the meaning is 12,173, meaning tcount (12,173)> t table (2,110), H0 rejected H2 is accepted. and the relationship of variables of back muscle mass and limb muscle explosive together towards Takraw Smash with a correlation coefficient of r = 0.959 where the significance was tested by the F-test and obtained a count of 91.60, meaning tcount (91.60)> t table ( 3.63) thus H0 is rejected and Ha is accepted. Based on the results of research and data processing using research statistical procedures, it was concluded that the Variables of Back Muscle Deficiency and Muscle Power had a significant relationship to Sepak Takraw Smash and could be applied to the Ekstra Kurikuler Sepak takraw SMA Negeri 1 Benai.Key Words: Flexibility, Leg Muscle Power, Smash Sepak Takraw